2019
DOI: 10.1038/s41416-018-0349-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 trial of olaparib and oral cyclophosphamide in BRCA breast cancer, recurrent BRCA ovarian cancer, non-BRCA triple-negative breast cancer, and non-BRCA ovarian cancer

Abstract: BACKGROUND: We conducted a Phase 1 study to evaluate safety and activity of olaparib tablets and oral cyclophosphamide. METHODS: Patients had metastatic breast cancer (BC) or recurrent high-grade serous ovarian cancer (HGSOC), performance status 0-2, and ≤3 lines of prior therapy. Patients were treated using a dose escalation strategy with cohort expansion once maximal tolerated dose (MTD) was determined. Dose level 1 (DL1): olaparib 300 mg bid, cyclophosphamide 50 mg on days 1, 3, and 5, weekly. DL2: olaparib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Contribution of aberrant DNA repair and DNA damage response in carcinogenesis and its response to treatments has been well established. Furthermore, the study of DNA repair components as oncological molecular markers has already reached clinical practice, including MGMT promoter methylation status (glioblastoma), BRCA1/2 mutations (breast and ovarian cancer), and MMR deficiency (colorectal, endometrial, ovarian, and other cancer types) …”
Section: Discussionmentioning
confidence: 99%
“…Contribution of aberrant DNA repair and DNA damage response in carcinogenesis and its response to treatments has been well established. Furthermore, the study of DNA repair components as oncological molecular markers has already reached clinical practice, including MGMT promoter methylation status (glioblastoma), BRCA1/2 mutations (breast and ovarian cancer), and MMR deficiency (colorectal, endometrial, ovarian, and other cancer types) …”
Section: Discussionmentioning
confidence: 99%
“…Early-phase clinical trials of olaparib demonstrated activity signals in patients with OC, with favorable tolerance and response rates. 58 , 111 113 Following these promising results, 114 a notable randomized placebo-controlled phase II trial, Study 19 (NCT00753545), evaluated olaparib as maintenance monotherapy for patients with platinum-sensitive recurrent OC. The median PFS was significantly longer in the olaparib arm compared with placebo (3.6 months longer, P < 0.001).…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, cancer cell death is the goal of PARPi treatment, and thus BRCA1/2 deficient patients have been the primary target population for treatment with this class of drugs. PARPi also shows promises in treating carriers of a PALB2 mutation, and has been tested with some success on triple-negative breast cancers, serous carcinomas of the ovaries, tumors with high replicative stress levels, and in combination with immune checkpoint blockade [62] , [63] , [64] , [65] , [66] . This cautiously offers hope for the development of novel combination therapies.…”
Section: Exploiting Dna Repair Deficiencies For Medicinementioning
confidence: 99%